α-Hederin Inhibits the Proliferation of Hepatocellular Carcinoma Cells via Hippo-Yes-Associated Protein Signaling Pathway - Chen, Tongqing; Sun, Dongdong; Wang, Qijuan; Zhou, Tingting; Tan, Jiani; Xu, Changliang; Cheng, Haibo; Shen, Weixing (Frontiers in Oncology, 2022)
Abstract: Aims: Yes-associated protein (YAP), a downstream protein in the Hippo signaling pathway, plays an important role in tumor proliferation, including in hepatocellular carcinoma (HCC). α-hederin, a monodesmosidic triterpenoid saponin isolated from Fructus akebiae, displayed anti-cancer effects on several cancer cell lines but the precise mechanism has not been ascertained. In the present study, we explored the effects of α-hederin on cell proliferation and apoptosis in human HCC cell lines and the underlying mechanisms. Main method: Cell proliferation and apoptosis were assessed using 5-ethynyl-2'-deoxyuridine staining, colony formation, flow cytometry. The expression patterns of components of Hippo signaling pathway and apoptotic genes were further examined via RT-qPCR and immunoblotting. A xenograft tumor model in nude mice was used to evaluate the anti-HCC effects of α-hederin in vivo. Results: α-hederin promoted the apoptosis and inhibited the proliferation of SMMC-7721 and HepG2 cells in vitro, and remarkably inhibited the tumor size and weight in the xenograft mouse model. Additionally, α-hederin increased the expression of pro-apoptosis proteins and suppressed the expression of anti-apoptosis proteins. Moreover, α-hederin treatment upregulated the expression of Hippo signaling pathway-related proteins and genes, while, effectively reduced the level of nuclear YAP, which resulted in the inhibition of proliferation and the induction of apoptosis of HCC cells. Finally, the effects of α-hederin on HCC cell proliferation and apoptosis were alleviated by XMU-MP-1, a Mst1/2 inhibitor in vitro.